Utilization of Palm Oil Fuel Ash (POFA) in Producing Lightweight Foamed Concrete for Non-structural Building Material. (2015) - Munir, Abdul; Abdullah,; Huzaim,; Sofyan,; Irfandi,; Safwan,
Abstract: The utilization of the materials from the industrial waste is an option to reduce the production cost of building materials that also will reduce the environmental impact from the waste. Industrial by-product from the palm oil mill in the form of palm oil fuel ash (POFA) can be used as a partial replacement for cement into the concrete mix due to its pozzolanic content. This study examines the role of POFA to replace the cement partially in foamed concrete production. Experiments have been conducted by replacing 10%, 20%, 30%, 40% and 50% of POFA by weight of Portland Pozzolan Cement. The results indicate a potential use of POFA in foamed concrete production. Despite a decline in the strength of concrete with the addition of POFA, the loss of concrete compressive strength by adding 50% POFA is only about 30-40% compared to that of control specimens. Based on its compressive strength, the foamed concrete with 20% POFA substitution is still applicable for non-structural building element such as concrete block for non-bearing wall. Indonesia as the largest palm oil industry produce a large amount of POFA that can be potentially utilized to produce low cost lightweight building material and also to reduce the environmental impact as well.